Efficacy of antiglaucoma fixed combination therapy versus unfixed components in reducing intraocular pressure: a systematic review. Issue 6 (6th May 2008) - Cox, J A; Mollan, S P; Bankart, J; Robinson, R
Abstract : Aim: To evaluate the efficacy of the fixed combination ocular hypotensive therapies compared with their non-fixed components used concomitantly for lowering intraocular pressure (IOP) in glaucoma and ocular hypertension. Methods: A systematic review of the literature, up to May 2007, without limits on year or language of publication was performed. Seven randomised controlled trials (n = 2, 083 eyes) were identified. Assessment of methodological quality was made using standardised criteria. Results were pooled quantitatively using meta-analysis methods, and statistical analysis was performed using STATA software. The difference in mean intraocular pressure (mm Hg) from baseline between the fixed combination and non-fixed component therapies was compared. Non-inferiority in terms of efficacy was set at an upper confidence limit of ⩽1.5 mm Hg for all time points (hour (Hr)0, Hr2 and Hr8) and evaluated at 12 weeks. Safety was evaluated from data on adverse events as reported in the included studies. Results: Of the 679 abstracts identified, seven randomised controlled trials met the selection criteria. The quality scores of included studies were high (mean of 29.4, maximum score 30). The mean differences (95% CI) and p values at 12 weeks were as follows: 0.200 mm Hg, (CI −0.106 to 0.507), p = 0.20 for Hr0, 0.393 mm Hg (CI 0.038 to 0.747), p = 0.03 for Hr2 and 0.501 mm Hg (CI 0.156 to 0.846), p = 0.004 for Hr8. Although both Hr2 and Hr8 showed statistical significance favouring the non-fixed combinations, the non-inferiority measure ⩽1.5 mm Hg upper confidence limit was not exceeded. Conclusions: Fixed combination therapies are equally safe and effective at lowering IOP as their non-fixed components administered concomitantly.